THE INTERTEXTUAL SIGNIFICANCE OF DEAR EVAN HANSEN NOVEL ADAPTATION ON THE ORIGINAL BROADWAY MUSICAL - Nabil Bakri (Anaphora : Journal of Language, Literary, and Cultural Studies, 2020)
In the process of adaptation, there are major changes in the process and the final project. Changes in creative adaptation is natural. The novel adaptation of Dear Evan Hansen was published in 2017 based on the acclaimed 2015 musical with the same title. Novels often adapted into films and musicals, but an adaptation from a Broadway musical into a novel is extremely rare. Author Val Emmich worked with the creators of the musical to ensure a successful passing of essence from play to novel, ensuring the foundation of the creation of the musical which is the matter of anxiety disorders among teenagers to remain visible throughout the novel.  Many scholars consider creative adaptation as less than the source material meaning that a creative adaptation translates into inferior product. This research scrutinized the process of creative adjustment in the novel through three distinct but interrelated perspectives based on the theory of adaptation by Linda Hutcheon: adaptation as a formal entity or product, adaptation as a process of creation, and adaptation as a process of reception. This research concludes that the novel adaptation transforms, deepens, and compliments the musical and its existence is justified as it contains intertextual significance.